KORELASI POLA MAKAN DAN TINGKAT KEJADIAN HIPERTENSI PADA LANSIA (STUDI KASUS PUSKESMAS WAAI KABUPATEN MALUKU TENGAH - Sitti R Latuamury; Nastain Pattimura; Abdul Thalib (STIKES Pasapua Ambon, 2022)
Introduction: Hypertension is one of the diseases experienced by the elderly. Hypertensive disease in the elderly in the Waai health center work area is caused by poor diet. Diet is a way or effort to carry out healthy eating activities so that the elderly avoid hypertension. Objective: aims to determine the relationship between diet and the incidence of hypertension in the elderly in the Waai health center work area. Methods: This study used a cross-sectional research design and sampling techniques using purposive sampling. Results: The study results said that (88.1%) of respondents had a lousy diet, and (64.4%) had stage II hypertension. The chi-square test results obtained a p = 0.003 (p<0.05), meaning that there is a relationship between diet and hypertension in the elderly. Recommendation: The elderly must maintain a good diet and regular exercise to prevent an increase in hypertension.